2010
DOI: 10.1007/s10545-010-9200-9
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid alterations of the serotonin product, 5‐hydroxyindolacetic acid, in neurological disorders

Abstract: Although patients with low cerebrospinal fluid (CSF) serotonin metabolite levels have been reported, inborn errors of the rate-limiting enzyme of serotonin synthesis (tryptophan hydroxylase, TPH) have not been described so far. In this study we aimed to evaluate CSF alterations of the serotonin metabolite 5-hydroxyindolacetic acid (5-HIAA) in patients with neurological disorders and to explore a possible TPH deficiency in some of them. A total of 606 patients (286 males, 320 females, mean age 4 years and 6 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 19 publications
2
29
0
Order By: Relevance
“…These results may be explained because neopterin is also produced intrathecally by different glial brain cells, acting as a possible link among inflammation, neurodegeneration and regeneration [24], [25]. These events can be found in primary inflammatory processes but are also commonly involved in some neurological acquired and unknown etiology diseases, in which neuroimaging reflects CNS damage.…”
Section: Discussionmentioning
confidence: 99%
“…These results may be explained because neopterin is also produced intrathecally by different glial brain cells, acting as a possible link among inflammation, neurodegeneration and regeneration [24], [25]. These events can be found in primary inflammatory processes but are also commonly involved in some neurological acquired and unknown etiology diseases, in which neuroimaging reflects CNS damage.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several authors have reported no difference for 5HIAA in CSF measured in autistic patients (for an overview see [17]), which is in contradiction to our routine determination of 5HIAA in CSF in patients with autistic disorders where we find a significant percentage of patients with low 5HIAA (unpublished observation). On the other hand, several other laboratories reported recently on isolated low 5HIAA level in CSF from patients with neurological disorders and neuro-psychiatric disturbances, including ASD (without identifying an underlying genetic cause) [25].…”
Section: Discussionmentioning
confidence: 99%
“…Agents that increase extracellular 5-HT levels, such as 5-hydroxytryptophan (5-HTP) and/or SSRIs, inhibit generalized tonic-clonic seizures as well as focal seizures, including hippocampal and lateral geniculate nucleus-kindled seizures and spontaneous seizures occurring after pilocarpine-induced SE, whereas, they increase absence seizures (for a review see Bagdy et al, 2007). In humans, a link between altered 5-HT, seizures and epilepsy is suggested by the finding of reduced levels of 5-HT metabolites in the cerebrospinal fluid of patients with seizure disorders (De Grandis et al, 2010), reduced in vivo 5-HT binding, mostly to 5-HT 1A receptors, in patients with chronic epilepsy (Merlet et al, 2004) and a possibly compensatory increase in 5-HT and 5-hydroxyindoleacetic acid (5-HIAA) content in cortex tissue resected from patients with pharmacoresistant epilepsy (Naffah-Mazzacoratti et al, 1996). Based on these findings, the suggestion has been made that modulation of serotoninergic function could represent an innovative approach to the treatment of AED-refractory epilepsy (Lo¨scher and Leppik, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, serotoninergic deficits increase seizure predisposition in mammals, whereas 5-HT can exert anticonvulsant effects (Bagdy et al, 2007). Accordingly, low levels of 5-HT metabolites were found in the cerebrospinal fluid of some patients with seizure disorders (De Grandis et al, 2010), and clinical observations suggest a potential seizuresuppressing effect of selective 5-HT reuptake inhibitors (SSRIs) (Albano et al, 2006). Other lines of evidence suggest that some forms of epilepsy may be related to decreased availability of the 5-HT precursor tryptophan (TRP) in the brain (Albano et al, 2006;Russo et al, 2009).…”
Section: Introductionmentioning
confidence: 99%